Mediating Civil Conflicts in Southeast Asia: Lessons from Aceh and Mindanao - John Lee Candelaria (JAS (Journal of ASEAN Studies), 2020)
Southeast Asia has been a hotbed of intractable civil conflicts motivated by several issues such as ethnicity, ideology, and historical injustice, among others. Despite the intractability, there have been instances when third-party assistance through mediation has been vital in achieving peace agreements in the region. Using the cases of the third-party mediation of the conflicts in Aceh, Indonesia and Mindanao, Philippines, this research identified the kinds of mediation and qualities of mediators that led to the achievement of peace agreements in these two cases. This research mainly focused on path dependence, critical junctures, and periodization approaches in the comparative analysis of Aceh and Mindanao third-party mediation through a qualitative examination that involved comparative process tracing (CPT), a two-step methodological approach that combines theory, chronology, and comparison. The results showed that the mediators instrumental to the Aceh and Mindanao peace agreements allayed the commitment issues of the negotiations and ensured the trust and confidence of the conflict parties. Thus, mediators should create relations of trust among parties and a mediation environment where the commitment fears are relieved through the promise of third-party monitoring.